A Curious Case of Sudden Refractive Change from Emmetropia to Myopia in a Post-LASIK Patient - Priyanka Gupta; Supreet Rai; Harleen Kaur; Aman Goyal (Delhi Journal of Ophthalmology)
The article discusses the potential ocular adverse effects of topiramate, an antiepileptic medication commonly used for migraine prevention. Topiramate-induced acute angle closure (TiAAC) is of particular concern as it can result in the sudden diminution of vision. The exact mechanism behind TiAAC is uncertain, but it is thought to involve prostaglandin release, leading to ciliary body effusion. In this case, a young male who had been emmetropic postmyopic LASIK surgery presented to us with sudden onset high myopia. Detailed history revealed that the patient had been recently using topiramate. On examination, there was anterior displacement of iris lens diaphragm. In-depth investigations confirmed it to be a case of TiAAC. The patient was advised to discontinue topiramate and was put on topical steroids, intraocular pressure-lowering agents, and cycloplegics which relieved his condition within 10 days.